Aplikasi Algoritma Floyd-Warshall untuk Mengoptimalkan Distribusi Listrik di PLN Kota Gorontalo - Usman, Susanti; Wiranto, Ifan; Nurwan, Nurwan (Scimadly Publishing, 2022)
This research deals with the application of the Floyd-Warshall algorithm and Floyd-Warshall plus in the optimization of electricity distribution network routes in Gorontalo City. The route optimization begins by representing the power poles and cable lengths into a graph. The graph used is a weighted graph where the road (related to the length of the cable) is represented as a weighted side and the electric pole is represented as a point. This graph consists of a set of electric poles totalling 40 points and a set of roads (cable lengths) totalling 46 sides. The results showed that the shortest path of the electricity distribution network is and the minimum cable network length is 9,040 m.